Traumatic Dental Injuries among Adolescents and Young Adults in Iași, Romania: Legal and Medical Perspectives - Giuvara Constantin Răzvan; Victor Vlad Costan; Otilia Boisteanu; Adina Armencia; Mihai Ciofu; Carina Balcos; Gabriela Calin; Diana Bulgaru Iliescu; Loredana Liliana Hurjui (MDPI AG, 2024)
Adolescents and young adults' active lifestyles make dental trauma a significant medical concern. Aim: This study aims to assess the etiology, frequency, and localization of dental and periodontal trauma in adolescents and young adults, along with these individuals' predisposition based on age, gender, and residence. Materials and Methods This retrospective study included 109 adolescents and young adults from a database of the Emergency and Oral and Maxillofacial Surgery department at "Sf. Spiridon" Hospital, Iasi, Romania. The collected data included demographic details, mechanisms of dental and periodontal trauma, treatment approaches, and clinical outcomes. Statistical analysis was performed using SPSS 26.0, with comparisons based on age, gender, and residence. Results: Enamel fractures (23.9%) and enamel-dentin fractures without pulp exposure (20.2%) were the most frequent dental injuries. Concussion (58.7%), subluxation (21.1%), luxation, avulsion (7.3%), and extrusion (5.5%) were common periodontal injuries. The anterior region of the dental arch accounted for the majority (60.6%) of injuries. Adolescents under 17 years were more prone to enamel-dentin fractures without pulp exposure (23.8%), enamel-dentin fractures with pulp exposure (20.6%), and root fractures (20.6%), while young adults over 18 years had a higher incidence of enamel fractures (32.6%) and crown-root fractures (30.4%). Falls (66.7%) were the predominant cause of trauma for female patients, whereas male patients were more often injured during sports activities (49.3%). The younger age group was 0.29 times more likely to sustain enamel-dentin fractures without pulp exposure (p = 0.049, OR = 0.291) and root fractures (p = 0.047, OR = 0.241). Conclusions: Traumatic dental injuries are more prevalent in young adults compared to adolescents, with falls and sports activities being the most common causes, particularly among males. These findings emphasize the need for targeted preventive programs aimed at reducing the incidence of dento-periodontal trauma in these age groups.